1972
DOI: 10.1093/bja/44.7.634
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Halothane on the Interactions Between Myocardial Contractility, Aortic Impedance, and Left Ventricular Performance I: Theoretical Considerations and Results

Abstract: The effects of halothane (1.0-1.5%) on myocardial contractility, systemic vascular resistance (representing the majority of impedance to oscillatory flow), and left ventricular performance, and the interactions of these functions have been studied in openchested dogs, artificially ventilated and maintained in a state of basal narcosis with chloralose and urethane. Halothane reversibly depressed myocardial contractility as estimated by three indices: maximum left ventricular (dP/dt)/IP, maximum left ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
27
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 56 publications
(29 reference statements)
6
27
0
Order By: Relevance
“…In contrast, PRYS-ROBERTS et al (1973), who studied hypertensive patients under halothane/nitrous oxide anaesthesia, found that variations in arterial pressure were attenuated both by i.v. and by oral practolol.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, PRYS-ROBERTS et al (1973), who studied hypertensive patients under halothane/nitrous oxide anaesthesia, found that variations in arterial pressure were attenuated both by i.v. and by oral practolol.…”
Section: Discussionmentioning
confidence: 95%
“…The discrepancy in results may possibly be explained by halothane, which reduces myocardial contractility (PRYS-ROBERTS et al 1972) and depresses baroreflexes (VATNER & BRAUNWALD 1975). Thus, the P-blocker may have potentiated the effect of halothane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have suggested that the ratio peak dPldtiI. P. is a better index of cardiac contractility since this ratio is independent of either changes in preload or afterload and varies only with changes in inotropism [Prys-Roberts et al, 1972;Jandhyala et al, 19771. This index of contractility was also not altered by homoharringtonine.…”
Section: Discussionmentioning
confidence: 99%
“…Halothane is the most thoroughly investigated agent and there are abundant reports of a dose-dependent depression of myocardial contractility, with increases in right and left ventricular filling pressures, both in animals (2) and in man (3, 4,5). The fall in cardiac output during halothane anaesthesia has been attributed to the impairment of cardiac function (6). Although the oxygen uptake is reduced, cardiac output is often reported to decrease to an even greater extent (7,8,9), leading to an increase in oxygen extraction.…”
mentioning
confidence: 99%